2013
DOI: 10.1590/s1517-86922013000600014
|View full text |Cite
|
Sign up to set email alerts
|

Análise do potencial mutagênico dos esteroides anabólicos androgênicos (EAA) e da l-carnitina mediante o teste do micronúcleo em eritrócitos policromáticos

Abstract: RESuMoIntrodução: Os esteroides anabólicos androgênicos são usados por pessoas que desejam aumentar sua massa muscular para obter um melhor desempenho nos esportes ou melhorar a aparência física. Os EAA são derivados sintéticos da testosterona, capazes de promover a hipertrofia das fibras musculares, aumentando a síntese proteica intracelular. A L-carnitina é um suplemento alimentar empregado para aumentar a produção energética por meio da oxidação de ácidos graxos. Embora haja trabalhos mostrando as proprieda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 24 publications
1
10
0
2
Order By: Relevance
“…The presence of BPV sequences in peripheral blood has already been described in the literature (Stocco dos Santos et al, 1998;Roperto et al, 2008;Diniz et al, 2009;Melo et al, 2011;Araldi et al, 2013b). The peripheral blood does not represent the first site of virus contact, according to the infection pathway commonly described (Florin et al, 2012).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The presence of BPV sequences in peripheral blood has already been described in the literature (Stocco dos Santos et al, 1998;Roperto et al, 2008;Diniz et al, 2009;Melo et al, 2011;Araldi et al, 2013b). The peripheral blood does not represent the first site of virus contact, according to the infection pathway commonly described (Florin et al, 2012).…”
Section: Discussionmentioning
confidence: 93%
“…The slides were stained with 20 μL propidium iodide (4 μg/mL) and visualized under an Axio Scope A1 fluorescent microscope (Carl Zeiss). Nucleoids were classified from 0 (without lesions) to 2 (major damage), according to Araldi et al (2013b), and the number of nucleoids observed per class was multiplied by the class value, resulting in a comet score. The statistical analysis was done by the Mann-Whitney test, with a significance level of 5%.…”
Section: Comet Assay Of Whole Bloodmentioning
confidence: 99%
“…For this reason, mutagen identification has been explored [13][14][15][16], since to avoid the long term exposure to these mutagens can be considered a protective method against cancer. Currently, it is known that several drugs [16][17][18], organic [19][20][21][22] and inorganic chemical compounds [23,24] and biological agents, including viruses [12,[25][26][27][28][29][30][31][32][33] are able to induce DNA damage.…”
mentioning
confidence: 99%
“…A primeira descrição do teste de micronúcleo surgiu com Schmid (1975Schmid ( ) em 1975 teste obteve êxito em relação as técnicas de monitoramento de aberrações cromossômicas, já que consiste numa técnica simples requerendo menos treinamento e perícia (ARALDI et al, 2013;). Para Fenech (2000, os micronúcleos possuem DNA Feulgenpositivo, não havendo nenhuma conexão com o núcleo principal, sendo que sua frequência pode aparecer elevada em células expostas a agentes carcinogênicos (ARALDI et al, 2013).…”
Section: Resultsunclassified